Draft genome sequences of two Thioalkalivibrio sulfidiphilus strains isolated from a pilot-scale haloalkaline biodesulfurization installation - Plugge, Caroline; Gupta, Suyash; Garcia Villa, Sarahi; Timmers, Peer; Muyzer, Gerard (American Society for Microbiology, 2025)
The genome sequences of two Thioalkalivibrio sulfidiphilus strains, SGAR-7 and SGAR-13, isolated from a pilot-scale haloalkaline biodesulfurization (BD) installation, are reported. The genomes comprise Flavocytochrome c sulfide dehydrogenase and SoxAX cytochromes, which are essential for respiration and thiosulfate oxidation, offering insights into Thioalkalivibrio’s role in BD.
Keywords: 24 Ciencias de la Vida::2414 Microbiología; ODS 9 - Industria, innovación e infraestructura; Thioalkalivibrio; sulfide; biodesulfurization